Background and descriptive features of rabies-suspected animals in Central Luzon, Philippines - Milagros R. Mananggit; Kazunori Kimitsuki; Nobuo Saito; Alyssa Marie G. Garcia; Patricia Mae T. Lacanilao; Joely T. Ongtangco; Cornelio R. Velasco; Maria Victoria D. Rosario; Maria Glofezita O. Lagayan; Kentaro Yamada; Chun-Ho Park; Satoshi Inoue; et al. (Tropical Medicine and Health, 2021)
Abstract Background The Philippines is one of the major endemic countries for canine rabies in Southeast Asia. However, detailed description and analysis of laboratory-confirmed animal rabies are limited. Highly accurate surveillance requires a thorough understanding of the target area-specific problems and obstacles. Therefore, we aim to describe and analyze the rabies suspect animals in Central Luzon, Philippines, to clarify the characteristics of management and clinical signs by conducting interviews with the owners. Methods We prospectively collected information on the rabies suspect animals submitted to the Regional animal laboratory in Central Luzon through passive laboratory-based rabies surveillance between 1st April 2019 and 30th September 2020. We performed active interviews directly or telephonically with the owner. The direct fluorescent antibody test was performed on the hippocampus, brain stem, and cerebellum for laboratory confirmation. Descriptive statistics were used to characterize the number of rabies cases according to management methods and characteristics of suspected animals during the observation period. Clinical symptoms of suspected rabid animals were analyzed by univariate logistic regression analysis. Results There were 292 sample submissions during the study period. Of these, 160 were positive for dFAT. Samples of pet animals (85.3%) provided by owners or their acquaintances (59.2%) accounted for the majority of laboratory confirmed cases. Case mapping showed that more rabies-suspected cases were sent from areas near the regional laboratory than from those far from the laboratory, despite the incidence of rabies being high in these areas. The management and clinical symptoms of 227 animal cases showed that most owners were managing their animals at home and were allowing them to roam outside (69.6%) and be unvaccinated (78.9%). Rabid animals were more likely to manifest aimless running, restlessness, and agitation. Conclusions Our study provided some features of animals with laboratory-confirmed rabies in Central Luzon. However, most of the samples were submitted from areas near the rabies diagnosis laboratory, and the number of samples submitted from remote areas was low. To improve the surveillance capacity, it is necessary to increase sample submissions from remote areas.